Estrogen Alleviates Acetic Acid-Induced Gastric or Colonic Damage via Both ER alpha- and ER beta-Mediated and Direct Antioxidant Mechanisms in Rats - YEGEN, BERRAK; ERCAN, FERİHA; ÖZDEMİR KUMRAL, ZARİFE NİGAR (SPRINGER/PLENUM PUBLISHERS, 2014)
In order to demonstrate the possible protective effects of estrogen receptor (ER)-alpha and ER beta receptor subtypes in the pathogenesis of colonic and gastric oxidant damage, experimental ulcer and colitis were induced by acetic acid, and the animals were randomly divided as colitis, ulcer, and their corresponding non-ulcer and non-colitis control groups. Each group of rats was treated intramuscularly with the vehicle, selective ER alpha agonist propylpyrazole-triol (1 mg/kg), ER beta agonist diarylpropionitrile (1 mg/kg), non-selective ER agonist 17 beta estradiol (E2; 1 mg/kg), or E2 plus non-selective ER antagonist ICI-182780 (1 mg/kg). The results revealed that induction of ulcer or colitis resulted in systemic inflammation as assessed by increased levels of plasma TNF-alpha and IL-6 levels. In both tissues, the presence of oxidant damage was verified by histological analysis and elevated myleoperoxidase activity. In the colitis and ulcer groups, both ER agonists and the non-selective E2 reversed the oxidative damage in a similar manner. These findings indicate that estrogen acts via both ER alpha- and ER beta-mediated and direct antioxidant mechanisms, where both ER subtypes play equal and efficient roles in the anti-inflammatory action of estrogen, in limiting the migration of neutrophils to the inflamed tissue, reducing the release and activation of cytokines and thereby alleviating tissue damage.
Keywords: estrogen receptor (ER)-alpha; ER beta; myeloperoxidase; TNF-alpha; colitis; ulcer; oxidative injury; RECEPTOR-ALPHA; SEX-HORMONES; PEPTIC-ULCER; TRAUMA-HEMORRHAGE; IMMUNE-RESPONSE; EXPRESSION; PROTECTION; GENDER; FEMALE; LIGAND